A Critical Reconsideration of its Role in Contemporary English Language Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Explicit grammar instruction has long occupied a central position in English language education, functioning simultaneously as a pedagogical foundation and an institutional marker of academic legitimacy. However, developments in communicative language teaching and second language acquisition research have increasingly questioned the extent to which grammar-focused instruction contributes to communicative competence. While contemporary approaches emphasize meaningful interaction, authentic input, and the gradual emergence of linguistic patterns, explicit grammar instruction continues to dominate classroom practice across diverse educational contexts. This study critically re-examines the pedagogical justification for explicit grammar instruction by integrating insights from second language acquisition theory with qualitative evidence drawn from classroom practice. Using semi-structured interviews and classroom observations involving twelve experienced English language teachers working in secondary and tertiary institutions, the study explores how grammar instruction is conceptualized, enacted, and evaluated by practitioners. The findings indicate that explicit grammar instruction persists primarily due to its symbolic, pragmatic, and institutional functions, providing structure, accountability, and a sense of progress for both teachers and learners[1]. At the same time, participants consistently acknowledged the limited transfer of explicitly taught grammar to spontaneous communicative use[2]. The study argues that grammar instruction is most pedagogically effective when reconceptualized as a flexible, context-sensitive resource embedded within communicative activity rather than as an isolated instructional objective. Implications for teacher education, classroom practice, and future research are discussed[3].